Anti-MRSA Activity of Actinomycin X2 and Collismycin A Produced by Streptomyces globisporus WA5-2-37 From the Intestinal Tract of American Cockroach (Periplaneta americana) - Chen, Zhiyu; Ou, Peiyu; Liu, Lingyan; Jin, Xiaobao (Frontiers in Microbiology, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is recognized as one of the serious pathogen that causes acquired infections worldwide. Its emerging need to discover novel, safe and potent anti-MRSA drugs. In this study, primary screening by anti-MRSA activity assay found one strain WA5-2-37 isolated from the intestinal tract of Periplaneta americana, exhibited great activity against MRSA ATCC 43300. The strain WA5-2-37 produced actinomycin X2 and collismycin A which showed strong inhibition of MRSA with minimum inhibitory concentration (MIC) values of 0.25 and 8 μg/mL. The structures of the pure compounds were elucidated by analysis of mass spectrometry (MS), 1H and 13C nuclear magnetic resonance (NMR). The strain WA5-2-37 was considered as Streptomyces globisporus on the basis of morphological characteristics, genotypic data, and phylogenetic analysis. This is the first reported naturally occurring strain of S. globisporus isolated from the intestinal tract of P. americana, whereas it has almost been found from plants, marine, and soil previously. Moreover, S. globisporus has not been reported to produce any anti-MRSA substances previously, such as actinomycin X2 and collismycin A. In conclusion, the insect-derived strain of S. globisporus WA5-2-37 was considered of great potential as a new strain of producing actinomycin X2, collismycin A or other anti-MRSA compounds.